Does dextran molecular weight affect the mechanical properties of whey protein/dextran conjugate gels? - Spotti, Maria Julia (2013)
Maillard reaction (MR) is one of the most studied methods to improve the functional properties of proteins so as to turn them into better food ingredients. The mechanical properties of whey protein isolate (WPI)/dextran (DX) mixed and conjugate (obtained by MR) gels were investigated. Dextrans with different molecular weight (MW: 6, 40 and 70 kDa) and various concentrations (3.6, 7.2 and 10.8% w/w) were studied. WPI/DX conjugates were obtained by controlled dry heating (60 C and 0.63 aw for 5 days). A decrease in the content of free amino group and an increase in colour parameters of WPI/DX conjugate systems revealed that MR had a higher progress for the lowest DX molecular weight and for the highest DX concentration. The mechanical properties (at the fracture point) of WPI/DX mixed gels were affected by DX concentration. On the other hand, unlike mixed gels, WPI/DX conjugate gels showed no fracture under the test conditions (80% deformation).